Short-term safety and tolerability profile of 5-methoxy-N,N-dimethyltryptamine in human subjects: a systematic review of clinical trials - Kwaśny, Aleksander; Wilkowska, Alina; Cubała, Wiesław Jerzy (Frontiers in Psychiatry, 2024)
Introduction: Psychedelic agents have regained the attention of pharmaceutical companies as promising treatments for depressive episodes. 5-Methoxy-N,N-dimethyltryptamine (5-MeO-DMT), an atypical psychedelic, is emerging as a potentially effective, novel rapid-acting antidepressant. In this systematic review, we analyze the safety and tolerability evidence from clinical trials. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines, electronic databases (PubMed, SCOPUS, Web of Science, EMBASE, and EBSCO) were searched from inception until 15 May 2024 to identify clinical trials (regardless of phase) reporting on short-term safety and tolerability profile of 5-MeO-DMT using the following keywords in various combinations: 5-methoxy-N, N-dimethyltryptamine, 5-MeO-DMT, safety, adverse, adverse reaction, side effects, tolerability, dropout, healthy volunteer, healthy participant, depression, major depressive disorder. Only studies written in English were considered. Results: Initial search yielded 100 records, out of which 3 met the inclusion criteria. These studies reported on the results from clinical trial phases I and I/II, with a total of 78 participants included; two studies involved healthy volunteers, and one included patients with treatment-resistant depression. Although the data is limited, it confirms a good short-term safety and tolerability profile for 5-MeO-DMT, with no serious adverse events (SAEs) reported. Furthermore, no drop-outs were reported. Conclusion: 5-MeO-DMT administration in human subjects presents favorable short-term safety and tolerability profile. Importantly, no SAEs have been documented, and no adverse events led to participant withdrawal from the studies There is a need for future randomized, double-blind, placebo-controlled trials with larger samples and follow-up to assess potential chronic adverse events.